Developing Teaching Capacity for Primary School Teachers in the Context of Education Innovation in Vietnam - Hoi, Huynh Tan (The journal of contemporary issues in business and government, 2021)
Student educational capacity is the component competencies in the competency framework of the teacher, especially for homeroom teacher, it is the core and essential competency in student education. Teachers play an important role in developing direct technical workforce for the country. Therefore, teaching capacity is a component of the pedagogical capacity and the most important capacity of the teacher. The teaching capacity of teachers in general and teachers in Thai Nguyen province in particular becomes the output standard, a criterion for building and evaluating teaching capacity in training and fostering pedagogy. This educational capacity includes the component competencies, via the survey process at primary schools in Thai Nguyen city, Thai Nguyen province, it shows the inequality between the competencies of the qualified teachers; via organizing experiential activities and coordinating the educational forces to educate students, it is clear that the 3 groups of weak competencies mostly focus on learning the characteristics of students and students' families. Schools have implemented measures to develop educational capacity for primary teachers, but these are still formalistic, fragmented and ineffective. The practical survey results in this paper will be the valid basis for proposing a number of measures to develop educational capacity for homeroom teachers working as teachers at primary schools in Thai Nguyen City, Thai Nguyen Province.